Impact of a Limosilactobacillus fermentum, Quercetin, and Resveratrol Nutraceutical on Fecal Microbiota Composition and Metabolic Activity in Healthy and Hypertensive Subjects - Jéssica Maria Alves Brasil; Nathalia Caroline de Oliveira Melo; Karoliny Brito Sampaio; Paulo César Trindade da Costa; Hatice Duman; Sercan Karav; Marcos dos Santos Lima; Evandro Leite de Souza; José Luiz de Brito Alves (Foods)
A promising strategy to improve the gut microbiome in hypertension is to target the gut microbiota. This study evaluated the effects of a potential nutraceutical product composed of three strains of Limosilactobacillus (L.) fermentum, quercetin, and resveratrol on the intestinal microbiome of healthy and hypertensive subjects. The nutraceutical product consisting of strains of L. fermentum 139, 263 and 296, fructooligosaccharides (200 mg), quercetin (160 mg), and resveratrol (150 mg) (LfQR) was added to the in vitro fecal fermentation process occurring for 48 h. Fecal samples of healthy and hypertensive subjects were allocated into four groups: (i) healthy controls (CTL); (ii) healthy controls with the addition of LfQR (CTL + LfQR); (iii) hypertensive (HTN) subjects; and (iv) hypertensive subjects with the addition of LfQR (HTN + LfQR). The diversity and composition of the fecal microbiota and the production of microbial metabolites were evaluated. CTL and HTN groups exhibited a distinct gut microbiota composition, as shown by the β-diversity assessment. The addition of the potentially nutraceutical-modulated β-diversity was similar between CTL and HTN groups, suggesting a similar gut microbiome composition after nutraceutical addition. The addition of the nutraceutical product increased the relative abundance of Enterobacteriaceae in the CTL group and that of Lachnospiraceae in the HTN group. The nutraceutical media showed higher levels of sugars (maltose, fructose, and glucose), lactic acid, ethanol, succinic acid, and acetic acid compared to the CTL and HTN media. Although the results are heterogeneous between healthy and hypertensive fermentation media, it was demonstrated that the nutraceutical formulation can modulate the intestinal microbiota and its metabolic activity.